The Use of Zoom Application to Increase Students’ Motivation in Learning English - Rezkya Abdal; A. Muliati; Fitri Radhiyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The purpose of this study was to determine the level of students’ motivation for the use of Zoom application in learning English. A mixed-method design was adapted in this study. The population of this research was the students of SMP Islam Wasuponda in the academic year 2022/2023. Through the total sampling technique, there were 32 students in eighth grade were chosen to be the sample of this research. The instruments of this research were a questionnaire and an interview. The research findings showed that the use of the Zoom application was effective to increase students’ motivation in learning English. It was proved by the level of students’ motivation where there were 53% of 32 students got high level of motivation, 28% of 32 students got moderate level of motivation, and 19% of 32 students got low level of motivation. There were three causes of increased students’ motivation as follows: Zoom has some features, Zoom is easy to access, and Zoom makes the students more confident.